Ekklesiologi Martin Luther Sebagai Dasar Tata Gereja Aliran Lutheran di Indonesia - Tiur Imeldawati; Rencan Charisma Marbun; Warseto Freddy Sihombing (Jurnal Teologi Cultivation, 2022)
Martin Luther as a great theologian has left a theological view that has a wide influence in the world, especially for the Lutheran churches. Martin Luther's ecclesiology has also been used as the basis for the Lutheran church order. What did Luther believe about ecclesiology? This is what this research tries to examine, and Luther's view has become the basis for Lutheran churches to carry out church programs related to their marturia, koinonia and diakonia. Has anything changed after hundreds of years have passed and how do Lutheran churches live up to Luther's belief in church life? This is what is studied in the research conducted by the author. This is interesting because the great influence of a Luther has been recognized by the world church.